The HARMONIE-AROME Model Configuration in the ALADIN-HIRLAM NWP System - Bengtsson, Lisa; Andrae, Ulf; Aspelien, Trygve; Batrak, Yurii; Calvo, Javier; de Rooy, Wim; Gleeson, Emily; Hansen-Sass, Bent; Homleid, Mariken; Hortal, Mariano; Ivarsson, Karl-Ivar; Lenderink, Geert; et al. (Monthly Weather Review, 2017)
The aim of this article is to describe the reference configuration of the convection permitting Numerical Weather Prediction (NWP) model HARMONIE-AROME which is used for operational short range weather forecasts in Denmark, Estonia, Finland, Iceland, Ireland, Lithuania, Netherlands, Norway, Spain and Sweden. It is developed, maintained and validated as part of the shared ALADIN-HIRLAM system by a collaboration of 26 countries in Europe and Northern Africa on short range meso-scale NWP. HARMONIE-AROME is based on the model AROME-France developed within the ALADIN consortium. Along with the joint modelling framework, AROME was implemented and utilised in both northern and southern European conditions by the above listed countries, and this activity has led to extensive updates to the model?s physical parameterizations. In this paper we present the differences in model dynamics and physical parameterizations compared with AROME-France, as well as important configuration choices of the reference, such as lateral boundary conditions, model levels, horizontal resolution, model time-step, as well as topography, physiography and aerosol data-bases used. Separate documentation will be provided for the atmospheric and surface data-assimilation algorithms and observation types used, as well as a separate description of the Ensemble Prediction System based on HARMONIE-AROME, which is called HarmonEPS.